About maintenance of concept «сriminal adaptation for stage» and another receptions of concealment (Journal of actual problems of jurisprudence, 2018)
In the article examined concepts of criminal adaptation for stage and another receptions of concealment of crimes. Under criminal adaptation for stage it is necessary to understand creation in place of incident by the interested face of situation falling short of to actually happening in this place. In the aspect of law-enforcement activity, a concealment must be examined as the dangerous phenomenon is social. It can show up in the acts of criminal behaviour, provide committing crime, prevent to the justice.Key words: criminal adaptation for stage, concealment of crimes, falsification, forgery, disguise, imitation.